2019
DOI: 10.1177/1465750319857017
|View full text |Cite
|
Sign up to set email alerts
|

Underpricing and Intellectual Capital Disclosure: Evidence from Indonesia

Abstract: In this study, we investigate the relationship between intellectual capital disclosure and underpricing. We did interviews and gave questionnaires to practitioners and academics to develop intellectual capital disclosure measurement methods (in this case, it is the weighted disclosure index). The analysis result of 189 companies which did initial public offerings in Indonesia during 2000–2014 shows that intellectual capital disclosure affects negatively on underpricing. It indicates that intellectual capital d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…They are quite relevant because the cultural and business environments in Indonesia and Malaysia are almost the same, seeing Indonesia and Malaysia are developing countries, in which Indonesia is still a lowermiddle-income country, while Malaysia is an upper-middle-income country (Djafar, 2012). Moreover, there is little research on intellectual capital disclosure in developing countries (Widarjo et al, 2019). On the other hand, there is a significant increase in the intellectual capital disclosure over three years, analyzed with external capital, human capital, and internal capital (Oliveras et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…They are quite relevant because the cultural and business environments in Indonesia and Malaysia are almost the same, seeing Indonesia and Malaysia are developing countries, in which Indonesia is still a lowermiddle-income country, while Malaysia is an upper-middle-income country (Djafar, 2012). Moreover, there is little research on intellectual capital disclosure in developing countries (Widarjo et al, 2019). On the other hand, there is a significant increase in the intellectual capital disclosure over three years, analyzed with external capital, human capital, and internal capital (Oliveras et al, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Chahal & Bakshi (2016) show that intellectual capital as a multidimensional scale is measured by human assets/human capital (HC), rational capital, and structural capital, which significantly contribute to intellectual capital. Furthermore, Widarjo et al (2019) found that intellectual capital has a negative effect on underpricing.…”
Section: Perceptionmentioning
confidence: 99%
“…In Indonesia, intellectual capital disclosure for each industry sector is relatively low, with an average of 50% of each component (Mukhibad & Setyawati, 2019;Purnomosidhi, 2006). In more detail, financial companies disclosed only 6.27% (M. W. Ningsih & Laksito, 2014), 22.29% for non-financial companies (Leonard & Trisnawati, 2015), 36.38% for the banking sector (Utama & Khafid, 2015), and 39.9% in newly listed companies (Widarjo et al, 2019). This low level of disclosure is due to the lack of awareness of the importance of intellectual capital disclosure in developing competitive advantage and improving company value (Suhardjanto & Wardhani, 2010).…”
Section: Introductionmentioning
confidence: 99%